2020
DOI: 10.3310/hta24400
|View full text |Cite
|
Sign up to set email alerts
|

Six versus 12 months’ adjuvant trastuzumab in patients with HER2-positive early breast cancer: the PERSEPHONE non-inferiority RCT

Abstract: Background The addition of adjuvant trastuzumab to chemotherapy has significantly improved outcomes for people with human epidermal growth factor receptor 2 (HER2)-positive, early, potentially curable breast cancer. Twelve months’ trastuzumab, tested in registration trials, was adopted as standard adjuvant treatment in 2006. Subsequently, similar outcomes were demonstrated using 9 weeks of trastuzumab. Shorter durations were therefore tested for non-inferiority. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 126 publications
(200 reference statements)
0
14
0
1
Order By: Relevance
“…In the PERSEPHONE study, designed to assess NI of the experimental group (6 months of trastuzumab), the clinically acceptable NI was defined as the 4-year disease-free survival being not worse by an absolute value of 3% than that of the standard group (12 months of trastuzumab), which was estimated to be 80%. [ 2 ] This 3% NI margin was decided before the start of the trial based on consensus from the trial development group that included patient and public involvement groups.…”
Section: Establishing the Margin Of Non-inferiority Or Equivalencementioning
confidence: 99%
See 2 more Smart Citations
“…In the PERSEPHONE study, designed to assess NI of the experimental group (6 months of trastuzumab), the clinically acceptable NI was defined as the 4-year disease-free survival being not worse by an absolute value of 3% than that of the standard group (12 months of trastuzumab), which was estimated to be 80%. [ 2 ] This 3% NI margin was decided before the start of the trial based on consensus from the trial development group that included patient and public involvement groups.…”
Section: Establishing the Margin Of Non-inferiority Or Equivalencementioning
confidence: 99%
“…The PERSEPHONE trial hypothesized that a shorter duration of trastuzumab therapy would be noninferior in terms of survival and offer benefits of being cheaper and having fewer adverse events. [ 2 ] Goyal et al . showed that azithromycin is noninferior to amoxicillin-clavulanic acid for treatment of respiratory exacerbations in children with bronchiectasis with the convenience of once-a-day dosing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nine respondents commented at some point in the questionnaire on low risk patients who are receiving paclitaxel for 12 weeks with concurrent trastuzumab continued for 12 months [8]. The number of patients receiving taxane-only chemotherapy within the PERSEPHONE trial is very small (35, 12 month patients and 38, 6 month patients) [11]. Hence, it is impossible to make any recommendations based on such limited data.…”
Section: Single-agent Taxane Regimensmentioning
confidence: 99%
“…Λόγω του σχετικά υψηλού κινδύνου υποτροπής, ακόμη και σε ασθενείς με όγκους N0 <1 cm, θα πρέπει να ληφθεί υπόψη, ιδιαίτερα σε ER-αρνητική νόσο85 .Στις περισσότερες μελέτες, η τραστουζουμάμπη χορηγήθηκε για 1 χρόνο, αν και στη Fin-HER παρόμοια βελτίωση επιτεύχθηκε με μόνο 9 εβδομάδες θεραπείας86 .Δεν εντοπίστηκε επιπρόσθετο όφελος για τη χορήγηση τραστουζουμάμπης διάρκειας 2 ετών στη δοκιμή HERA87 . Σε λίγες μελέτες συγκρίθηκε η βραχύτερη έναντι της συνήθους 12μηνης χορήγησης της τραστουζουμάμπης, αλλά μόνο η μεγαλύτερη δοκιμή Persephone μπόρεσε να δείξει τη μη κατωτερότητα του βραχύτερου 6μηνου σχήματος, αν και αυτό δεν μπορούσε να αποδειχθεί στις άλλες μελέτες88,89 .Επομένως, η συνήθης διάρκεια συνεχίζει να είναι 1 έτος, αν και σε εξαιρετικά επιλεγμένους ασθενείς χαμηλού κινδύνου, οι οποίοι λαμβάνουν χημειοθεραπεία ανθρακυκλίνης/ ταξάνης, μπορεί να συζητηθεί η μείωση της διάρκειας χορήγησης της τραστουζουμάμπης στους 6 μήνες.Η τραστουζουμάμπη είναι συνήθως καλά ανεκτή, αν και μπορεί να προκαλέσει καρδιακή δυσλειτουργία, συνήθως αναστρέψιμη. Η στοιχειώδης καρδιακή λειτουργία (εκφραζόμενη από το κλάσμα εξώθησης αριστερής κοιλίας) είναι απαραίτητη πριν την έναρξη της θεραπείας και απαιτείται περιοδικός έλεγχος της καρδιακής λειτουργίας (συνήθως κάθε 3-4 μήνες) κατά τη διάρκεια της θεραπείας18 .Λόγω της καρδιοτοξικότητάς της, η τραστουζουμάμπη συνήθως δεν πρέπει να χορηγείται μαζί με ανθρακυκλίνη.…”
unclassified